Efforts to Increase the Ability to Introduce Numbers Through Playing Number Cards at Fathonah Early Childhood Education - Badriyah, Siti; Haryono , Mimpira (CV. Generasi Insan Rafflesia, 2022)
The purpose of this study was to determine the increase in the ability to recognize numbers through playing number cards at PAUD Fathonah, Seluma Regency. Classroom Action Research (CAR) which is focused on classroom situations, or commonly known as classroom action research procedures that use cycle forms. Based on the results of the research and discussion, the researchers drew the conclusion that through learning efforts to increase the ability to introduce numbers through playing number cards at PAUD Fathonah in Talang Perapat Village, Kec. Seluma. This increase can be seen from the increase in the percentage after the implementation of the actions in cycle I and cycle II. Implementation of the action in the first cycle, the percentage shown from the first cycle was 45.71%. The implementation of the actions in Cycle II showed an increase compared to the actions in Cycle I. The percentage of achievement results in Cycle II was 87.71% in the Very Good Developing criteria, meaning that it achieved the research success criteria of 75% - 100%.